Primary Immunodeficiency Disorder in Children of Bangladesh: A Cross-Sectional Study from a Tertiary Care Hospital (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Primary immunodeficiency diseases (PIDDs) are a heterogeneous group of inherited disorders resulting from intrinsic defects in the immune system, leading to increased susceptibility to recurrent and severe infections. Although advances in diagnostic techniques have improved detection rates in high-income settings, early diagnosis remains a significant challenge in low- and middle-income countries. Therefore, a better understanding of the clinical and laboratory profiles of PIDD is essential to facilitate timely diagnosis and improve patient outcomes, particularly in resource-limited settings such as Bangladesh.  Objective: To make a survey on the demographic, clinical, and laboratory characteristics of PIDD cases diagnosed among children at a tertiary care hospital in Bangladesh.Methods: A total of 62 clinically suspected PIDD patients from paediatric departments of Bangladesh Medical University were evaluated between March 2020 to January 2021. Quantitative immunoglobulin assays and flow cytometric immunophenotyping were performed to confirm diagnoses.Results: Of the 62 suspected cases, 14 (23%) were laboratory-confirmed as PIDDs. The median age at diagnosis was 21 months, and the male-to-female ratio was 1:1. Predominantly antibody deficiencies were the most frequent category (64.3%), followed by combined immunodeficiencies (35.7%). Common variable immunodeficiency (CVID) and agammaglobulinemia were the leading subtypes. Recurrent pneumonia (68%) and recurrent use of intravenous antibiotics (76%) were the most frequent warning signs.Conclusion: Predominantly antibody deficiencies represent the major category of PIDDs in this study, consistent with global patterns. Enhanced awareness, expanded diagnostic access, and establishment of a national PIDD registry are essential for early detection and improved patient management in Bangladesh.J Com Med Col Teachers’ Asso Jan 2026; 30(1): 46-49